A high ionic conductivity membrane and its preparation method and application
By attaching lithium-containing substances to the blended filler of the lithium-ion battery separator and embedding an adhesive porous layer, the shortcomings of the existing separator in terms of ionic conductivity, heat resistance and negative electrode reducing gas are solved, and efficient conductivity improvement and long-life battery performance are achieved.
Patent Information
- Application Number
- CN202410821885.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The existing lithium-ion battery separators have limitations in improving ionic conductivity and heat resistance, and the commonly used coating structures have poor effect on blocking negative electrode reducing gases.
By attaching lithium-containing substances to the through holes of the blended filler and embedded in the adhesive porous layer, a stable spatial structure is formed, and the ionic conductivity and cycle life of the lithium-ion battery are improved, while the heat resistance of the separator and the ability to block negative electrode reducing gas are improved.
The high ionic conductivity and long cycle life of lithium-ion batteries are achieved, the heat resistance of the diaphragm and the ability to block negative electrode reducing gases are enhanced, and the defects and performance of the coating structure are avoided.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of secondary batteries, and in particular to a high ionic conductivity diaphragm and a preparation method and application thereof. Background Art
[0002] As the concept of environmental protection gradually takes root in people's minds, the new energy industry represented by lithium-ion batteries has gradually increased its share in the traditional energy market. The current market has higher and higher requirements for the endurance of lithium batteries, which has led to the continuous increase in the energy density of lithium batteries. However, the result is that the internal components of lithium batteries need to provide higher ion conductivity and strong heat resistance, thereby improving the overall performance of lithium batteries.
[0003] As one of the key components of the battery, the diaphragm is responsible for isolating the positive / negative electrodes to prevent short circuits and the transmission channel of lithium ions. Currently, most common diaphragms introduce ceramics and high molecular polymers as coatings to improve the ionic conductivity of the battery and the heat resistance of the diaphragm, and at the same time can block some of the reducing gases generated by overheating of the negative electrode of the battery. However, this method has a limited effect on improving the ionic conductivity of the battery, and its main effect is to enhance the heat resistance of the diaphragm and block the reducing gas of the negative electrode.
[0004] In this regard, the Chinese invention patent with announcement number CN110171833B introduces gel electrolyte with lithium salt into the battery, which can effectively improve ion conductivity. The porous silica nanofibers are also beneficial to increase heat resistance, but the amount of lithium salt attached to the surface of silica by impregnation is limited, and the improvement of ion conductivity is not obvious, and the loose gel structure is not conducive to improving heat resistance and blocking negative electrode reducing gas. The Chinese invention patent with announcement number CN114597591B can effectively improve the heat resistance of the diaphragm and block negative electrode reducing gas by coating a film coating with a dense interior and a smooth surface on the battery diaphragm. The ceramic particles treated with surface silanization and the polymer matrix that absorbs lithium salts are synergistically coupled to improve lithium ion conduction, but the polymer has limited adsorption of lithium salts, and the improvement of ion conductivity is always limited. The Chinese invention patent with announcement number CN114725620A significantly improves the initial effect by setting a lithium replenishing layer on one side of the diaphragm base film and adding a conductive agent to the lithium replenishing layer, which can achieve rapid and complete lithium replenishment. However, lithium powder may remain in the diaphragm, and the structure of the lithium powder collapses after releasing lithium ions, causing defects in the lithium replenishing layer, which directly affects the performance of the diaphragm. Summary of the invention
[0005] The purpose of this application is to provide a high ionic conductivity diaphragm and its preparation method and application, which can effectively improve the ionic conductivity and overcome the shortcomings of the prior art by introducing a coating that can adsorb a large amount of lithium ions into the diaphragm system while meeting the requirements of heat resistance of the battery diaphragm, blocking the reducing gas of the negative electrode and not destroying the diaphragm structure.
[0006] To achieve the above purpose, the embodiment of the present application adopts the following technical solution: a high ionic conductivity diaphragm, comprising:
[0007] A basement membrane, wherein the basement membrane is a porous material;
[0008] An adhesive porous layer is arranged on at least one side surface of the base film, the adhesive porous layer includes a heat-resistant resin and a blended filler, the blended filler has a through-hole structure, a lithium-containing substance is attached to the through-holes of the blended filler, and the blended filler includes a spherical filler and a rod-shaped filler.
[0009] In the above technical scheme, the embodiment of the present application can improve the ionic conductivity of the lithium-ion battery and also improve the cycle life of the battery by attaching lithium-containing substances in the through holes of the blended filler; the particles of the blended filler are added into the adhesive porous layer by embedding to form a stable spatial structure, the strength and heat resistance of the soft adhesive porous layer are increased, and the adhesive porous layer is not easily damaged during the cycle of the lithium battery.
[0010] Further, according to an embodiment of the present application, the base membrane is one or more of a porous membrane, a porous aromatic skeleton material, a non-woven fabric, a molecular sieve or a mesoporous material.
[0011] Further, according to an embodiment of the present application, the heat-resistant resin is one or more of polyvinylidene fluoride, aramid, furan-based polyamide, polyimide, and polyacrylonitrile.
[0012] Further, according to an embodiment of the present application, the blended filler is one or more of aluminum hydroxide, magnesium hydroxide, calcium hydroxide, alumina, silica, boehmite, clay, and molecular sieve.
[0013] Further, according to an embodiment of the present application, the average particle size of the spherical filler is 0.01~5μm.
[0014] Further, according to an embodiment of the present application, the rod-shaped filler satisfies the following relationship:
[0015] 4≤h / b≤20;
[0016] Here, h is the average length of the major axis of the rod-shaped filler contained in the adhesive porous layer, and b is the average length of the minor axis of the rod-shaped filler contained in the adhesive porous layer.
[0017] Further, according to an embodiment of the present application, the adhesive porous layer satisfies the following relationship:
[0018] 5≤a / d≤12;
[0019] Here, a is the average thickness of the adhesive porous layer on one side, and d is the average particle size of the spherical filler contained in the adhesive porous layer.
[0020] Further, according to an embodiment of the present application, the lithium-containing substance is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, and lithium tetrafluoroborate.
[0021] In order to achieve the above object, the present application also discloses a method for preparing a high ionic conductivity membrane, comprising the following steps:
[0022] Dissolving the heat-resistant resin to form a glue solution, and dispersing the blended filler into the glue solution at a high speed to form a mixed coating solution;
[0023] coating the mixed coating liquid on the base film to form a coating film;
[0024] The coating film is placed in a coagulation bath, and after the mixed coating liquid undergoes phase separation, the heat-resistant resin is solidified and forms a stable spatial structure with the blended filler.
[0025] After multiple water washing and high-temperature drying, the coagulation liquid and water are removed to obtain the high ion conductivity diaphragm.
[0026] Further, according to an embodiment of the present application, the method of attaching a lithium-containing substance in the through-holes of the blended filler includes:
[0027] The blended filler, toluene and 3-aminopropyltriethoxysilane are mixed and reacted to obtain an amination blended filler;
[0028] Add L-glutamic acid, EDC.HCl, and an amino-modified blend filler to morpholinoethanesulfonic acid, and then add N-hydroxysulfosuccinimide to react to obtain an amino-modified blend filler;
[0029] The amino acidized blended filler and NaOH are added into deionized water for ultrasonic dispersion, and the lithium-containing substance is added into the dispersion. After the reaction is completed, the lithium-containing substance is attached to the through holes of the amino acidized blended filler.
[0030] Further, according to an embodiment of the present application, the coagulation bath includes a good solvent and a phase separation agent.
[0031] Further, according to an embodiment of the present application, the good solvent is one or more of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
[0032] Further, according to an embodiment of the present application, the phase separation agent is one or more of water, ethanol, isopropanol, and glycerol.
[0033] In order to achieve the above objectives, the embodiments of the present application also disclose an application of a high ionic conductivity diaphragm in a lithium battery.
[0034] Compared with the prior art, the present application has the following beneficial effects: the present application can improve the ionic conductivity of lithium-ion batteries and also improve the cycle life of batteries by attaching lithium-containing substances in the through holes of the blended filler; the particles of the blended filler are added into the adhesive porous layer by embedding to form a stable spatial structure, the strength and heat resistance of the soft adhesive porous layer are increased, and the adhesive porous layer is not easily damaged during the cycle of the lithium battery. DETAILED DESCRIPTION
[0035] In order to make the purpose and technical solution of the present invention clearly and completely described, and the advantages more clearly understood, the embodiments of the present invention are further described in detail below. It should be understood that the specific embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are only used to explain the embodiments of the present invention, and are not used to limit the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, it should be noted that the terms "center", "middle", "upper", "lower", "left", "right", "inner", "outer", "top", "bottom", "side", "vertical", "horizontal" and the like indicating directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "one", "first", "second", "third", "fourth", "fifth", "sixth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0037] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0038] For the purpose of simplicity and illustration, the principles of the embodiments are mainly described by reference to examples. In the following description, many specific details are proposed to provide a thorough understanding of the embodiments. However, it is obvious that for those of ordinary skill in the art, these embodiments may not be limited to these specific details in practice. In some instances, known methods and structures are not described in detail to avoid making these embodiments unnecessarily difficult to understand. In addition, all embodiments can be used in combination with each other.
[0039] The present application discloses a high ion conductivity diaphragm, comprising a base film and an adhesive porous layer disposed on at least one side of the base film, wherein the adhesive porous layer comprises a heat-resistant resin and a blended filler, wherein the blended filler has a through-hole structure, and a lithium-containing substance is attached to the through-holes of the blended filler.
[0040] For the above technical solution, the present application can improve the ionic conductivity of lithium-ion batteries and also improve the cycle life of batteries by attaching lithium-containing substances in the through holes of the blended filler; the particles of the blended filler are added into the adhesive porous layer by embedding to form a stable spatial structure, and the strength and heat resistance of the soft adhesive porous layer are increased. During the cycle of the lithium battery, the adhesive porous layer is not easily damaged.
[0041] 1. Basement membrane
[0042] The base film in this application adopts porous materials, specifically refers to materials with pores or voids, and a network structure composed of interconnected or closed holes, including porous membranes, porous aromatic skeleton materials, organic polymer materials such as non-woven fabrics, inorganic materials such as molecular sieves and mesoporous materials, and composite porous materials formed by stacking several materials. The so-called porous membrane has a continuous pore structure, and gas or liquid can pass through the material itself.
[0043] The porous film itself is required to have a certain heat resistance, and the polyolefin film has the ability to close the holes at high temperatures. From the perspective of high heat resistance, the polypropylene film has a higher closed-cell temperature and can be used as a preferred option.
[0044] The polypropylene porous membrane can be manufactured by the following method: a polypropylene polymer is first used to prepare a polyolefin casting sheet with high orientation and low crystallinity, and after low-temperature stretching to form micro defects such as silver streaks, a high-temperature annealing is used to open the defects, thereby obtaining a microporous film with uniform pore size and uniaxial orientation.
[0045] By superimposing a functional coating on the porous membrane, the diaphragm can be enhanced or have new functions added. As a functional coating, for example, a high ion conductivity, a polymer coating with lithium ions, or a composite coating of a polymer resin and a filler with lithium ions can be added. As a polymer coating for lithium ions, polyacrylic acid, polyvinylidene fluoride, polyacrylonitrile resin, etc. with composite lithium ions can be selected; as a filler with lithium ions, materials such as silicon oxide, aluminum oxide, molecular sieves, etc. with surface modification can be selected. The superposition of multifunctional coatings can be achieved by coating, dipping, spraying, etc.
[0046] Considering the ion conductivity of the porous base membrane, the air permeability value is generally preferably 50~200s / 100cc.
[0047] 2. Adhesive porous layer
[0048] In the present invention, the adhesive porous layer is a spatial network structure, and a large number of micropores inside are interconnected, and can pass gas or liquid like a basement membrane.
[0049] The adhesive porous layer is disposed on one or both sides of the porous membrane. Considering the heat resistance of the separator and the cycle performance of the battery, it is more beneficial to the battery performance to dispose it on both sides of the porous base membrane.
[0050] In order to ensure the heat resistance of the separator and the cycle performance of the battery, the thickness of the adhesive porous layer is maintained at 0.5~5μm, preferably 2~4μm; greater than 0.5μm can ensure the heat resistance of the separator, and less than 5μm can maintain the space occupied by the positive and negative electrodes of the lithium battery.
[0051] Considering the shuttle efficiency of lithium ions, the porosity of the battery adhesive porous layer is 30%~70%. Below 70%, the stability of the skeleton structure of the porous layer can be guaranteed; above 30%, the shuttle efficiency of lithium ions can be guaranteed.
[0052] The pore size distribution of the adhesive porous layer is 50~500nm. When the pore size is below 500nm, the local distribution uniformity of the pores can be guaranteed, the difference in adhesion is small, and the lithium ion permeability can be guaranteed; when the pore size is above 50nm, lithium ions can easily pass through and clogging is not likely to occur.
[0053] In order to ensure the adhesiveness and heat resistance of the adhesive porous layer, the total density of the adhesive porous layer on both sides of the porous base film is 4.0~20.0g / m 2 , single side: 2.0~10.0g / m 2 .
[0054] In the present invention, the adhesive porous layer is disposed on both sides of the porous base film. If it is disposed on only one side of the porous base film, the separator may curl due to the rigid structure of the adhesive porous layer, making it difficult to handle.
[0055] 3. High heat resistant resin
[0056] In the present invention, the adhesive porous layer comprises a high heat-resistant resin including polyvinylidene fluoride, aramid, furan-based polyamide, polyimide, polyacrylonitrile and the like.
[0057] The high heat-resistant resin is preferably furan-based polyamide, which ensures the mechanical strength and heat resistance of the separator. The adhesive porous layer containing furan-based polyamide has higher heat resistance than the adhesive porous layer not containing furan-based polyamide.
[0058] The mass proportion of the high heat-resistant resin in the adhesive porous layer is 10wt%~50wt%.
[0059] 4. Blending fillers
[0060] In the present invention, the blended filler is composed of inorganic materials, and the inorganic filler can be hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide, or oxides such as aluminum oxide and silicon dioxide, as well as particulate matter such as boehmite, clay, and molecular sieves. The filler can be selected alone or in combination of two or more.
[0061] The shape of the filler is any one of spherical, rod-shaped, linear, and amorphous, or a combination of several thereof. From the perspective of battery safety, a combination of spherical and rod-shaped fillers is preferred.
[0062] If spherical fillers are used, the average particle size is maintained at 0.01~5μm, preferably 0.1~0.5μm. In the volume-based particle size distribution, the particle size at which the volume accumulation from the small particle size side reaches 50% is called the average particle size (D50) of the spherical filler. If the average particle size d is less than 0.01 μm, the filler particles may produce a large number of agglomerated particles in the adhesive porous layer, destroying the network structure supporting the adhesive porous layer. If the average particle size d is greater than 5μm, the spherical filler cannot fully fill the gaps between the rod-shaped fillers, the diaphragm has poor puncture resistance, and the battery cycle performance is poor.
[0063] If a rod-shaped filler is used, the average length of the long axis of the rod-shaped filler is maintained at 0.4-20 μm, preferably 0.8-10 μm; the average length of the short axis of the rod-shaped filler is maintained at 0.1-1 μm, preferably 0.2-0.6 μm.
[0064] The filler particles are added into the adhesive porous layer by embedding, forming a stable spatial structure with the adhesive porous layer, thereby increasing the strength of the soft adhesive porous layer. At the same time, the embedded filler can effectively improve the heat resistance of the adhesive porous layer while having little effect on the adhesion of the adhesive porous layer.
[0065] The proportion of the blended filler in the total amount of the high heat-resistant resin and the blended filler is greater than 40wt% and less than 90wt%. The proportion of the spherical filler in the blended filler is greater than 10wt% and less than 80wt%.
[0066] If the content of the blended filler is more than 40wt%, the mechanical strength of the adhesive porous layer can be guaranteed; if the content of the blended filler is less than 90wt%, the adhesive porous layer can maintain adhesion and network structure. If the spherical filler accounts for more than 10wt% of the blended filler, the gaps between the rod-shaped fillers can be effectively filled; if the spherical filler accounts for less than 80wt% of the blended filler, the rod-shaped filler is in the majority, and a stable spatial structure can be formed.
[0067] 5. Relationship between blended filler and adhesive porous layer
[0068] The rod-shaped filler in the blended filler needs to satisfy the following relationship:
[0069] 4≤h / b≤20;
[0070] Here, h is the average length of the major axis of the rod-shaped filler contained in the adhesive porous layer, and b is the average length of the minor axis of the rod-shaped filler contained in the adhesive porous layer.
[0071] Specifically, in order to ensure the ability of the adhesive porous layer to resist lithium dendrites, the ratio of the average length of the major axis of the rod-shaped filler to the average length of the minor axis is h / b≥4. If h / b<4, the rod-shaped filler cannot support the network structure of the adhesive porous layer; if h / b>20, the major axis of the rod-shaped filler may protrude from the adhesive porous layer, preferably above 5 and below 12.
[0072] In addition, regarding the adhesive porous layer, the ratio of its average thickness a to the average particle size d of the spherical filler is greater than 5 and less than 12, so that the particles are kept in the porous layer in an inlaid form, and the diaphragm exhibits good adhesion. If a / d is less than 5, a large amount of filler particles may be exposed on the surface of the porous layer, and the adhesion of different parts of the diaphragm is likely to differ. If a / d is greater than 12, it is difficult for the diaphragm adhesive porous layer to reach the desired thickness. From the above viewpoint, it is preferably greater than 6 and less than 10.
[0073] 6. Lithium-containing substances
[0074] In the present invention, both the spherical and rod-shaped fillers have through holes, and lithium-containing substances are attached to the holes. The lithium-containing substances are composed of lithium salts, such as lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, etc. Each lithium salt can be used alone or in combination. The lithium salt is required to have good electrochemical stability, not corrode the current collector, be easily soluble in carbonate organic solvents, and have a high ionic conductivity in the lithium salt solution at room temperature.
[0075] In this application, by attaching lithium-containing substances to the through holes of the blended filler, the through holes of the filler particles can increase the passage of lithium ions, which helps to improve the ionic conductivity. If the lithium-containing substance is directly mixed into the filler for coating, it is easy to occupy the space of other substances in the coating layer, and the lithium-containing substance may remain in the diaphragm. After releasing lithium ions, it causes part of its own structure to collapse, and the coating film has defects, which directly affects the performance of the diaphragm, including the heat resistance of the diaphragm, the ability to block negative electrode reducing gas, the ability to block lithium dendrites, the air permeability of the diaphragm, etc. Therefore, in this application, the lithium-containing substance is filled into the filler without affecting the performance of the filler or destroying the diaphragm structure, and it can better play the advantages of the lithium-containing substance (increasing the ionic conductivity of the battery).
[0076] Furthermore, the proportion of lithium-containing substances in the total amount of the blended filler is greater than 5wt% and less than 70wt%. If the content of lithium-containing substances is greater than 5wt%, the lithium salt can improve the transmission efficiency of lithium ions and the ion conductivity during the battery cycle. If the content of lithium-containing substances is less than 70wt%, the lithium-containing substances will not block the pore structure of the filler and can serve as a natural transmission channel for lithium salts. Furthermore, the through holes of the filler can adsorb lithium-containing substances, but when the content of lithium-containing substances accounts for more than 50wt%, the adsorption efficiency of the filler on the lithium-containing substances is greatly reduced.
[0077] 7. Method for attaching lithium-containing substances
[0078] The method of attaching the lithium-containing material to the through-holes of the blended filler includes:
[0079] The blended filler, toluene and 3-aminopropyltriethoxysilane are mixed and reacted to obtain an amination blended filler;
[0080] Add L-glutamic acid, EDC.HCl, and an amino-modified blend filler to morpholinoethanesulfonic acid, and then add N-hydroxysulfosuccinimide to react to obtain an amino-modified blend filler;
[0081] The amino acidized blended filler and NaOH are added into deionized water for ultrasonic dispersion, and the lithium-containing substance is added into the dispersion. After the reaction is completed, the lithium-containing substance is attached to the through holes of the amino acidized blended filler.
[0082] 8. Physical properties of high ionic conductivity membrane
[0083] While ensuring the heat resistance of the diaphragm and the space occupied by the positive and negative electrodes of the lithium battery, the overall thickness of the diaphragm is 3-16um; considering the ion conductivity and mechanical strength of the diaphragm, the air permeability value is generally preferably 50~200s / 100cc.
[0084] Considering the adhesion with the electrode, mechanical strength, and shuttling efficiency of lithium ions, the porosity of the diaphragm is 30%~60%. Below 60%, the mechanical strength of the diaphragm can be guaranteed, and above 30%, the shuttling efficiency of lithium ions can be guaranteed.
[0085] The thermal shrinkage of the diaphragm is less than 10% in both MD and TD directions at 105°C. Within this range, the shape stability and closed-cell effect of the diaphragm can improve the safety of the battery.
[0086] 9. Preparation method of high ionic conductivity membrane
[0087] The heat-resistant resin is dissolved to form a glue solution, and the blended filler is dispersed therein at a high speed to form a mixed coating solution;
[0088] coating the mixed coating liquid on the base film to form a coating film;
[0089] The coating film is placed in a coagulation bath, and after the mixed coating liquid undergoes phase separation, the heat-resistant resin is solidified and forms a stable spatial structure with the blended filler.
[0090] After multiple water washing and high-temperature drying, the coagulation liquid and water are removed to obtain the high ion conductivity diaphragm.
[0091] The solvent in the coating solution is preferably a polar solvent that can dissolve the high heat-resistant resin, such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, etc.
[0092] Among them, the coagulation bath includes a good solvent and a phase separation agent. The good solvent is one or more of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. The type and percentage of the phase separation agent play a decisive role in the pore structure of the adhesive porous layer. The phase separation agent can be selected from water, ethanol, isopropanol, glycerol, etc. From the perspective of good pore-forming effect, a mixed solution is formed by more than 40wt% of the solvent and less than 60wt% of the phase separation agent in the coagulation bath. It is preferred that the proportion of the good solvent in the coagulation bath is lower than the proportion of the good solvent in the coating solution. From the perspective of pore-forming efficiency, the proportion of water is 20wt%~90wt%.
[0093] In the coating liquid, in order to form a good pore structure, the mass proportion of the high heat-resistant resin is 1wt%~15wt%.
[0094] In the coating liquid, the addition of the blended filler can effectively improve the heat resistance and mechanical strength of the adhesive porous layer, while having little effect on the adhesion of the adhesive porous layer. The blended filler accounts for 50wt%~90tw% of the total amount of the blended filler and the high heat-resistant resin.
[0095] The coating liquid is preferably applied by micro-gravure coating, and the coating liquid is applied to both sides of the porous base membrane at the same time.
[0096] 10. Non-aqueous secondary batteries
[0097] The battery is mainly composed of a positive electrode, a negative electrode, and the above-mentioned non-aqueous secondary separator, and an electrolyte is injected, and the battery is then packaged to obtain a battery structure.
[0098] The positive electrode is composed of a lithium-containing active material and a conductive agent and a binder that binds the two and bonds them to the current collector.
[0099] The positive electrode active material is a metal oxide containing a lithium salt, including lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0100] The adhesive may be polyvinylidene fluoride, polymethyl methacrylate, or polyacrylonitrile.
[0101] The conductive agent can be a traditional conductive agent such as carbon black, conductive graphite, carbon fiber, etc. and a new conductive agent such as carbon nanotubes, graphene, etc.
[0102] The current collector can be 5~20um aluminum foil, titanium foil, etc.
[0103] Since the coating of the aforementioned high ion conductivity diaphragm contains a blend of high heat-resistant resin and rod-shaped and spherical fillers, the diaphragm has high safety and excellent thermal performance, and lithium nickel cobalt manganese oxide with high energy density can be used as the positive electrode material.
[0104] The negative electrode consists of an active material and a conductive agent as well as a binder that binds the two and bonds them to the current collector.
[0105] The negative electrode materials are mainly active substances that can adsorb or insert lithium ions, including carbon materials, silicon-carbon composites, lithium alloys, lithium metals, etc.
[0106] The adhesive is polyvinylidene fluoride, styrene butadiene rubber, etc.
[0107] The conductive agent can be a traditional conductive agent such as carbon black, conductive graphite, carbon fiber, etc. and a new conductive agent such as carbon nanotubes, graphene, etc.
[0108] The current collector can be 5~20um aluminum foil, titanium foil, etc.
[0109] The electrolyte is a solution obtained by dissolving a lithium salt in one or more solvents such as cyclic carbonate, chain carbonate, carboxylic acid ester, etc.
[0110] Lithium salts can be selected from LiPF6, LiClO4, LiBF4, LiAsF6, LiFSI, etc.
[0111] The solvent includes cyclic carbonates such as ethylene carbonate and propylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and carboxylates include methyl acetate, ethyl acetate, methyl formate, methyl propionate, ethyl propionate and the like.
[0112] The high ion conductivity diaphragm of the present invention has good wettability to various electrolytes and contains a blend of high heat-resistant resin and rod-shaped and spherical fillers. The diaphragm has high safety, excellent thermal performance, and can inhibit the flammability of the electrolyte.
[0113] The coating of the high ionic conductivity diaphragm contains a blended filler, and lithium salts are attached to the through holes of the filler particles. These lithium salts can enter the electrolyte and effectively improve the ionic conductivity; or when the lithium salts in the electrolyte are reduced, these lithium salts can also effectively maintain the ionic conductivity.
[0114] The material for packaging the battery can be an aluminum shell, a steel shell, an aluminum-plastic film, or a steel-plastic film. The battery shape can be square, cylindrical, or soft-pack. The present invention mostly uses a cylindrical shape.
[0115] The manufacturing method of the battery comprises: winding or stacking the positive electrode, the negative electrode and the non-aqueous secondary separator of the present invention, hot pressing and shaping the battery core, packaging it in a packaging material, and finally injecting an electrolyte.
[0116] The technical solution of the present application is further described below by listing embodiments and comparative examples, but the present application is not limited to these embodiments. Example 1
[0117] Diaphragm production:
[0118] The blended filler is composed of spherical and rod-shaped porous fillers. The average particle size of the spherical filler is 0.4um, the average length of the long axis of the rod-shaped spherical filler is 3um, the average length of the short axis is 0.5um, and the ratio of spherical to rod-shaped fillers is 2:8.
[0119] The porous blend filler was amino-treated with 3-aminopropyltriethoxysilane and L-glutamic acid.
[0120] As the lithium salt material contained in the through-holes of the porous blend filler, lithium bis(fluorosulfonyl)imide is selected; the blend filler is immersed in the lithium bis(fluorosulfonyl)imide solution, taken out and dried after a certain period of time; the ratio of lithium salt input to porous blend filler is 6:4.
[0121] As a high heat-resistant resin, furan polyamide (molar ratio 1 / 1.05, weight average molecular weight greater than 300,000) was prepared by melt polymerization using dimethyl 2,5-furandicarboxylate and decanediamine, which was referred to as resin A. Resin A was dissolved in N-methylpyrrolidone.
[0122] The porous blend filler is dispersed in the above solution to form a coating solution.
[0123] The solid content of the coating liquid is 10%, and the porous blended filler accounts for 80% of the total amount of the coating liquid and the furan polyamide.
[0124] The coating liquid was coated in equal amounts on both sides of a polyethylene porous membrane (thickness 9 μm, air permeability 120 s / 100 cc, porosity 50%), immersed in a coagulation bath (water: N-methylpyrrolidone: dimethylformamide = 50:40:10 (mass ratio)) to solidify, then immersed in a coagulation bath (water: N-methylpyrrolidone: dimethylformamide = 80:10:10 (mass ratio)) to secondary solidify, then washed with water and dried to obtain a diaphragm having an adhesive porous layer formed of furan polyamide and a porous blend filler on both sides of the polyethylene porous membrane. The thickness of the adhesive porous layer is 4 μm.
[0125] Preparation of negative electrode: artificial graphite rich in negative electrode active material, styrene-butadiene rubber as a binder, carbon black as a conductive agent and an appropriate amount of water are used to prepare negative electrode slurry. The negative electrode slurry is coated on a 10 μm copper foil as a current collector, and after drying and pressing, a negative electrode with a negative electrode active material layer is obtained.
[0126] Preparation of positive electrode: Lithium iron phosphate as positive electrode active material, carbon black as conductive agent, and polyvinylidene fluoride as binder are stirred to form slurry. The positive electrode slurry is coated on a 20μm aluminum foil as a current collector, and after drying and pressing, a positive electrode with a positive electrode active material layer is obtained.
[0127] The positive and negative electrodes are welded with tabs, and the positive electrode, separator, negative electrode, and separator are wound in order to manufacture the battery cell, which is then hot-pressed and shaped, then encapsulated in a steel shell material, and finally injected with electrolyte. The electrolyte is 1M LiPF6-ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (mass ratio 3 / 5 / 2). The hot pressing conditions are set at 3MPa, hot pressing temperature 95°C, and hot pressing time 5min. Example 2
[0128] In this example, the average thickness of the adhesive porous layer was changed to 2.4 μm, and the rest was the same as in Example 1, so that a separator and a test battery of Example 2 were produced. Example 3
[0129] In this embodiment, the ratio of the average length of the major axis to the average length of the minor axis of the rod-shaped filler is 10, and the rest is the same as in Embodiment 1, and the separator and test battery of Embodiment 3 are manufactured. Example 4
[0130] In this embodiment, the ratio of spherical fillers to rod-shaped fillers is 5:5, and the rest is the same as in Embodiment 1, and the separator and test battery of Embodiment 4 are manufactured. Example 5
[0131] In this embodiment, the ratio of lithium salt input to porous blend filler is 4:6, and the rest is consistent with that in Embodiment 1, and the diaphragm and test battery of Embodiment 5 are manufactured. Example 6
[0132] In this embodiment, 1,1-difluoroethylene is polymerized into polyvinylidene fluoride (weight average molecular weight 500,000) (referred to as resin B) to replace resin A. The rest is the same as in embodiment 1, and the diaphragm and test battery of embodiment 6 are produced. Example 7
[0133] In this embodiment, acrylonitrile is polymerized into polyacrylonitrile (weight average molecular weight 2 million) (referred to as resin C) to replace resin A. The rest is the same as in embodiment 1, and the diaphragm and test battery of embodiment 7 are produced.
[0134] [Comparative Example 1]
[0135] The blended filler added in this comparative example is a non-porous filler, and the rest is consistent with Example 1, and the diaphragm and test battery of Comparative Example 1 are prepared.
[0136] [Comparative Example 2]
[0137] In this comparative example, the blended filler was changed to a rod-shaped filler, and the rest was the same as in Example 1, so that a separator and a test battery of Comparative Example 2 were prepared.
[0138] [Comparative Example 3]
[0139] In this comparative example, the blended filler was changed to a spherical filler, and the rest was the same as in Example 1, and a separator and a test battery of Comparative Example 3 were prepared.
[0140] [Comparative Example 4]
[0141] In this comparative example, only furan polyamide was dissolved in N-methylpyrrolidone to form a coating solution, and no blending filler was added. The rest was consistent with Example 1, and a diaphragm and a test battery of Comparative Example 4 were prepared.
[0142] [Comparative Example 5]
[0143] In this comparative example, no lithium salt was used and was not filled in the through holes of the blended filler. The rest was consistent with Example 1, and a separator and a test battery of Comparative Example 5 were produced.
[0144] [Comparative Example 6]
[0145] In this comparative example, lithium bis(fluorosulfonyl)imide was ground into powder and directly mixed with the blended filler, but not filled into the through holes of the blended filler. The rest was consistent with Example 1, and the diaphragm and test battery of Comparative Example 6 were manufactured.
[0146] The raw materials and proportions of Examples 1-7 and Comparative Examples 1-6 are summarized in Table 1.
[0147] Table 1
[0148]
[0149] The performance tests of the diaphragms and test batteries prepared in the above Examples 1-7 and Comparative Examples 1-6 are performed as follows:
[0150] 1. Thickness of adhesive porous layer
[0151] The average thickness of the adhesive porous layer is the average thickness of the separator minus the average thickness of the porous base film. If the adhesive porous layer is provided on both sides of the porous base film, the average thickness of the separator minus the average thickness of the porous base film is divided by 2.
[0152] To measure the thickness of the diaphragm and the porous base film, eight layers of diaphragms were overlapped and 10 points were randomly selected on an area of 10 cm x 10 cm using a Mahr thickness gauge. The average was then divided by 8 to obtain the thickness.
[0153] 2. Surface density
[0154] The average surface density of the adhesive porous layer is the average surface density of the separator minus the surface density of the porous base film. If the adhesive porous layer is provided on both sides of the porous base film, the average surface density of the separator minus the average surface density of the porous base film is divided by 2.
[0155] The surface density of the diaphragm and porous base film was determined by stacking 8 10 cm x 10 cm diaphragms on a microbalance and weighing them. The area was removed and then divided by 8 to obtain the surface density.
[0156] 3. Filler particle size distribution
[0157] The filler was dispersed in pure water, stirred, and then ultrasonically dispersed. The particle size was measured using a laser particle size distribution instrument (Beettersize 2000).
[0158] In the volume-based particle size distribution, the particle size at which the volume accumulation from the smaller particle size side reaches 50% is called the median particle size (D50), which is the volume average particle size of the filler.
[0159] 4. Filler infrared characterization
[0160] The filler was dried at low temperature as a test sample; the filler was added to a beaker containing deionized water, and sufficient hydrochloric acid was added, stirred and allowed to stand for washing and drying as a test sample, and spectrally pure KBr pellets were used for analysis using FTIR (Gangdong-650).
[0161] Infrared spectrum test range 4000~400cm -1 The main functional groups of each substance in the filler have their own characteristic absorption peaks. The existence of the characteristic absorption peaks and the changes in peak height (transmittance) are the basis for the existence and quantity changes of each substance in the filler.
[0162] 5. Determination of Li content
[0163] The filler was washed and dried, and the ground and dried sample was placed in a conical flask, and hydrochloric acid was added to dissolve the sample. After the sample was completely dissolved, the volume was fixed; the supernatant was taken by centrifugation, and HNO3 solution and hydrochloric acid were added to the supernatant, and the volume was fixed to obtain the test solution, and the content of Li element was determined using a Plasma3000 ICP spectrometer.
[0164] The analysis line of Li can be selected from 670.784 nm, 610.365 nm and 323.263 nm. Considering the precision and accuracy comprehensively, 670.784 nm is preferably selected as the analysis line. The content of Li element is analyzed and determined to determine the amount of lithium salt adsorbed in the filler.
[0165] 6. Heat shrinkage
[0166] The mechanical stretching direction of the diaphragm is called the longitudinal direction (MD), and the direction perpendicular to the mechanical direction is called the transverse direction (TD). When the temperature is high, the diaphragm will shrink in the longitudinal and transverse directions under high-temperature baking, and the molecular chains will tighten.
[0167] A 10cm x 10cm membrane was sandwiched between A4 papers and placed in an oven at high temperature for 1 hour. After taking it out, the longitudinal and transverse shrinkage ratios of the membrane were tested.
[0168] 7. Battery ion conductivity
[0169] The test method of conductivity is as follows: at room temperature 25°C, button cell, frequency 0-100000Hz, disturbance voltage 5 mV, ion conductivity unit σ / mS cm-1. Metrohm Autolab PGSTAT302N electrochemical workstation is used to measure ion conductivity.
[0170] 8. Battery cycle performance test
[0171] Through the charge and discharge cycle test, the change of the charge and discharge capacity of the lithium battery with the number of charge and discharge cycles can be directly observed. The battery cycle performance is measured using the Xinda Energy S100-20-40-single-channel charge and discharge tester.
[0172] Cyclic experiment test: charge at a constant current of 0.3A to a cut-off voltage of 3.65 V, switch to a constant voltage of 3.65V and charge to 0.1A, let stand for 10 minutes, then discharge at a constant current of 0.3A to a cut-off voltage of 2.5V, and the cycle ends after 200 times.
[0173] The filler characterization test results are summarized in Table 2.
[0174] Table 2
[0175]
[0176] As shown in Table 2, the results of Examples 1, 4, 5, 7 and Comparative Examples 1-2 at 3443 cm -1 、961 cm -1 Absorption peaks appear at all places, indicating the presence of Si-OH groups. Before acidification, the transmittances of Examples 1, 4, 5 and Comparative Example 1 gradually decrease, indicating that the positions where Si-OH groups in the filler are replaced by lithium salts gradually decrease and are close to the filler after acidification, that is, only a small amount of lithium salts are present in the filler, which is manifested as the number of Si-OH groups gradually increasing; the transmittances of the Si-OH absorption peaks of the fillers after acidification in all Examples and Comparative Examples are not much different and are all small, indicating that the positions in the filler originally replaced by lithium salts are occupied by Si-OH groups again after acidification, that is, there is basically no lithium salt, which is consistent with the situation before the filler is amino acidized.
[0177] The physical properties and evaluations of the batteries are summarized in Table 3.
[0178] Table 3
[0179]
[0180] As shown in Table 3, the filler of Comparative Example 6 has no Li element content, and the ionic conductivity of the corresponding diaphragm is basically the same as that of Examples 1-7, indicating that the direct mixing of lithium-containing substances and fillers is indeed effective in improving the ionic conductivity of the battery, but its heat resistance has greatly declined, and after the battery has been charged and discharged, the diaphragm releases lithium ions, causing part of its structure to collapse, so that the ability of the diaphragm to block the negative electrode reducing gas is destroyed, and the corrosion rate of the positive electrode material is accelerated. In addition, due to structural defects in the diaphragm, its ability to block lithium dendrites will also decline, which will directly affect the cycle performance of the battery. It can be seen from the table that the cycle performance of Comparative Example 6 is relatively the worst; and filling the lithium-containing substance into the filler can improve the ionic conductivity and optimize the cycle performance of the battery without affecting the performance of the filler. The situation of Comparative Examples 2-3 is worse than that of Example 1, indicating that the result of blending fillers with different morphologies is slightly better than that of a single morphology; Comparative Examples 4-5 show that if lithium salts are not added, the battery cycle performance is poor.
[0181] Although the above describes the illustrative specific implementation methods of the present application so that technicians in this technical field can understand the present application, the present application is not limited to the scope of the specific implementation methods. For ordinary technicians in this technical field, as long as various changes are within the spirit and scope of the present application defined and determined by the attached claims, all application creations using the concept of the present application are protected.
Claims
1. A high ionic conductivity membrane, characterized in that: include: A basement membrane, wherein the basement membrane is a porous material; An adhesive porous layer, the adhesive porous layer is arranged on at least one side surface of the base film, the adhesive porous layer comprises a heat-resistant resin and a blended filler, the blended filler has a through-hole structure, and a lithium-containing substance is attached to the through-holes of the blended filler; the blended filler comprises a spherical filler and a rod-shaped filler; The method of attaching a lithium-containing substance in the through-holes of the blended filler includes: The blended filler, toluene and 3-aminopropyltriethoxysilane are mixed and reacted to obtain an amination blended filler; Add L-glutamic acid, EDC.HCl, and an amino-modified blend filler to morpholinoethanesulfonic acid, and then add N-hydroxysulfosuccinimide to react to obtain an amino-modified blend filler; The amino acidized blended filler and NaOH are added into deionized water for ultrasonic dispersion, and the lithium-containing substance is added into the dispersion. After the reaction is completed, the lithium-containing substance is attached to the through holes of the amino acidized blended filler.
2. A high ionic conductivity membrane according to claim 1, characterized in that: The heat-resistant resin is one or more of polyvinylidene fluoride, aramid, furan-based polyamide, polyimide, and polyacrylonitrile.
3. A high ionic conductivity membrane according to claim 1, characterized in that: The blended filler is one or more of aluminum hydroxide, magnesium hydroxide, calcium hydroxide, aluminum oxide, silicon dioxide, boehmite, clay, and molecular sieve.
4. A high ionic conductivity membrane according to claim 1, characterized in that: The average particle size of the spherical filler is 0.01-5 μm.
5. A high ionic conductivity membrane according to claim 1, characterized in that: The rod-shaped filler satisfies the following relationship: 4≤h / b≤20; Here, h is the average length of the major axis of the rod-shaped filler contained in the adhesive porous layer, and b is the average length of the minor axis of the rod-shaped filler contained in the adhesive porous layer.
6. A high ionic conductivity membrane according to claim 1, characterized in that: The adhesive porous layer satisfies the following relationship: 5≤a / d≤12; Here, a is the average thickness of the adhesive porous layer on one side, and d is the average particle size of the spherical filler contained in the adhesive porous layer.
7. A high ionic conductivity membrane according to claim 1, characterized in that: The lithium-containing substance is one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, and lithium tetrafluoroborate.
8. A method for preparing a high ionic conductivity membrane as claimed in claim 1, characterized in that: The following steps are involved: Dissolving the heat-resistant resin to form a glue solution, and dispersing the blended filler into the glue solution at a high speed to form a mixed coating solution; coating the mixed coating liquid on the base film to form a coating film; The coating film is placed in a coagulation bath, and after the mixed coating liquid undergoes phase separation, the heat-resistant resin is solidified and forms a stable spatial structure with the blended filler. After multiple water washing and high-temperature drying, the coagulation liquid and water are removed to obtain the high ion conductivity diaphragm.
9. The method for preparing a high ionic conductivity membrane according to claim 8, characterized in that: The coagulation bath includes a good solvent and a phase separation agent.
10. The method for preparing a high ionic conductivity diaphragm according to claim 9, characterized in that: The good solvent is one or more of N-methylpyrrolidone, dimethylformamide and dimethylacetamide.
11. The method for preparing a high ionic conductivity membrane according to claim 9, characterized in that: The phase separation agent is one or more of water, ethanol, isopropanol and glycerol.
12. Use of a high ionic conductivity diaphragm as claimed in any one of claims 1 to 7 or a high ionic conductivity diaphragm prepared by the method for preparing the high ionic conductivity diaphragm as claimed in any one of claims 8 to 11 in a lithium battery.
Citation Information
Patent Citations
A silica nanofiber-based gel composite electrolyte and its preparation method
CN110171833B
Lithium-ion battery separator, its preparation method and application
CN114597591B
Lithium supplement diaphragm of lithium battery, preparation method of lithium supplement diaphragm and lithium battery
CN114725620A
Nanoparticle coated lithium ion battery diaphragm and preparation method thereof
CN108336279A
Battery isolating membrane, preparation method thereof and secondary battery
CN114267923A